Sustainable Agricultural Technologies and Livelihoods of Smallholder Farmers in Uganda - Yvonne A Okoth; Maurice Osewe; Aijun Liu (Chemical Engineering Transactions)
In sub-Saharan African countries like Uganda, the majority of smallholder farmers rely on agriculture for their livelihood. They face climate shock that poses a more significant challenge to their agricultural practices. This study aims to investigate whether sustainable agricultural technologies at the farm level significantly contribute to smallholder farmers' livelihoods with a focus on crop diversification. The study used the Uganda National Panel Survey (UNPS) 2018-19 data. It employed an econometric model to analyze the impacts of various sustainable agricultural practices on the farmers livelihood index. Results reveal that the livelihood index is distinguished by tropical livestock unit, value of other assets, literacy index, dependency ratio, marital status of the household head as well as the log of maize, cassava and beans yields. The study also revealed that household index was affected by the sex and age of the household head, the use of improved seed, improved cassava varieties, no burning and the use of organic manure. Adopting and using these practices increases yields and income among vulnerable smallholder farmers., These findings highlight the vital need to adopt sustainable agricultural technologies to improve farmers' ability to adapt, increase agricultural productivity and address the problem associated with crop production sustainability. This will help meet the second goal of the sustainable development goals in Africa.